Effect Of Ethanol Leaf Extract Bangunbangun (Plectranthus amboinicus (Lour.) Spreng) As Preventive And Curative Rhodamine B Toxic Effects On The Kidney Histopathology White Rat (Rattus norvegicus) - Rianita Situmorang; Melva Silitonga (JBIO: jurnal biosains (the journal of biosciences), 2015)
This study aimed to obtain empirical data on weight changes, changes in the ratio of kidney and renal histopathologic state of rats given ethanol extract of leaves bangunbangun and Rhodamine B on preventive and curative treatment. This study was an experimental study with non factorial completely randomized design. In this study using 40 rats were divided into 8 treatment, the control group were given CMC 1%, Rhodamine B dose of 980 mg / kg bw, and preventive curative doses of ethanol extract of the leaves bangunbangun 350 mg / kg bw, 700 mg / kg bw, and 1050 mg / kg bw. Making the histopathology using hematoxylin-eosin staining. The data obtained and analyzed by ANOVA LSD test using SPSS version 16.0. The results showed that the ethanol extract of leaves bangunbangun treatment preventive dose of 350 mg / kg bw and 700 mg / kg bw gives a significant effect on weight gain, whereas treatment curative ethanol extract of leaves bangunbangun give a significant effect on weight gain at a dose of 350 mg / kg bw and 1050 mg / kg bw. Ethanol extract of the leaves bangunbangun treatment preventive dose of 350 mg / kg bw and 700 mg / kg bw gives a significant effect on the ratio of the kidney, whereas treatment curative ethanol extract of leaves bangunbangun give a significant effect on the ratio of the kidney with a dose of 350 mg / kg bw, 700 mg / kg bw, and 1050 mg / kg bw. Bangunbangun leaf ethanol extract at a dose of 350 mg / kg bw, 700 mg / kg bw, and 1050 mg / kg bw on preventive and curative treatment did not show any significant effect on glomerular diameter. Bangunbangun ethanol extract of the leaves can also prevent and reduce the toxic effects on the kidney.   Keywords: Plectranthus amboinicus, body weight, ratio of kidney, diameter of the glomerulus, the kidney